THE INFLUENCE OF ETHNO-NATIONAL LOBBIES ON THE US FOREIGN POLICY: HISTORY OF THE UKRAINIAN DIASPORA - I. D. Loshkariov; D. A. Parenkov; A. A. Sushentsov (Vestnik MGIMO-Universiteta, 2018)
The article examines the political potential of the Ukrainian ethnic lobby in US foreign policy. Proceeding from the fact that ethnic lobbies in the US are able to overcome the institutional system of checks and balances, the authors try to establish the extent and limits of the influence of the Ukrainian lobby.The given lobby is based on a small-numbered Ukrainian diaspora in the US, which was formed as a result of four waves of migration from the territory of modern Ukraine, due to various reasons. As a result, the Ukrainian diaspora in the United States has developed as a highly heterogeneous and multi-layered community. The main organization of the Ukrainian diaspora is the Ukrainian Committee of the Congress of America, which is an umbrella structure for organizations of economic, cultural and political profile, as well as for associations of veterans, women and youth. The Ukrainian diaspora in the US uses the following tools for political purposes. First, the diaspora organizations strive to encourage the activities of their low- and middle-ranking civil servants to form an optimal agenda. Diaspora immigrants from experts and media persons are connected to this process. Secondly, the Ukrainian diaspora has established cooperation with other Eastern European diasporas. The cooperation allows the Ukrainian Americans to use electoral potential in the states of the Northwest and Midwest of the United States and to take joint initiatives in communication with the Congress. Together, Eastern European diasporas have some influence on the American foreign policy process when it comes to the Congress, but the scope of influence should not be exaggerated. However, the demand for anti-Russian arguments is formed within the American establishment, that brings the agenda of the Ukrainian diaspora to the forefront of foreign policy debate. This allows us to conclude that the potential for political influence of the Ukrainian ethnic lobby in the United States is limited without a suitable international context.